THE ROLE OF GAMIFICATION IN ENHANCING MOTIVATION IN FRENCH LANGUAGE LEARNING - Narzulloyeva Dilfuza Bahriddin qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
ABSTRACT: This paper investigates the role of gamification in enhancing learner motivation in the context of French as a Foreign Language (FLE) education. As modern language classrooms increasingly integrate digital and interactive tools, gamified learning environments have emerged as a promising strategy to stimulate engagement and sustain interest among learners. This study reviews theoretical perspectives on motivation, particularly Self-Determination Theory, and examines empirical evidence on the use of gamification tools such as Kahoot, Duolingo and Quizlet. It also explores practical classroom applications through task-based gamified exercises designed to support vocabulary retention, grammar practice, and oral fluency. The findings suggest that gamification significantly boosts both extrinsic and intrinsic motivation, providing learners with a sense of autonomy, competition, and enjoyment. The paper concludes with pedagogical implications and suggestions for further research in technology-enhanced language instruction.